1986
DOI: 10.1111/j.1365-2133.1986.tb05741.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of hidradenitis suppurativa in women using combined antiandrogen (cyproterone acetate) and oestrogen therapy

Abstract: The effects of combined treatment with the antiandrogen, cyproterone acetate, and ethinyl oestradiol on four women with long-standing hidradenitis suppurativa have been investigated. The condition was controlled successfully in all patients with 100 mg/day cyproterone acetate using the reversed sequential regimen; lowering the antiandrogen to 50 mg/day caused deterioration. Before treatment, plasma testosterone levels were within the normal range, but plasma androstenedione values were raised and sex hormone b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
6

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 5 publications
0
55
0
6
Order By: Relevance
“…In 1986, Sawers et al [130] reported on the effectiveness of the antiandrogen cyproterone acetate combined with estrogen in four female HS patients. However, a doubleblind controlled trial comparing ethinyloestradiol 50 lg/cyproterone 50 mg with ethinyloestradiol 50 lg/ norgestrel 500 lg showed no difference between the two groups.…”
Section: Cyproterone Acetatementioning
confidence: 99%
“…In 1986, Sawers et al [130] reported on the effectiveness of the antiandrogen cyproterone acetate combined with estrogen in four female HS patients. However, a doubleblind controlled trial comparing ethinyloestradiol 50 lg/cyproterone 50 mg with ethinyloestradiol 50 lg/ norgestrel 500 lg showed no difference between the two groups.…”
Section: Cyproterone Acetatementioning
confidence: 99%
“…10 Other case series have also shown therapeutic benefit for antiandrogens in some patients with HS. [11][12][13] Finasteride is a competitive inhibitor of the type II 5␣-reductase enzyme, which converts testosterone to dihydrotestosterone, resulting in decreased serum dihydrotestosterone levels. Type II 5␣-reductase is found in hair follicles, whereas type I 5␣-reductase is present in both hair follicles and apocrine glands.…”
Section: Commentmentioning
confidence: 99%
“…Eher enttäuschend ist die Wirkung der Retinoide [21]. Die antiandrogene Therapie mit Cyproteronacetat, 1986 von Mortimer [19] und Sawers [23] propagiert, erfährt in der neueren Literatur keine Bestätigung und ist natürlich nur bei Frauen einsetzbar. Die dauerhaftesten Resultate zeigt die plastisch-chirurgische Entfernung des gesamten apokrinen Drüsenareals [22].…”
Section: Acne Inversa · Hidradenitis Suppurativa · Dapsonunclassified
“…Entsprechend empfehlen Mortimer [19] und Sawers [23] die antiandrogene Therapie mit Cyproteronacetat. Jemec [11] und Barth [2] finden hingegen keine Hinweise auf eine vermehrte kutane Virilisierung bzw.…”
Section: Diskussionunclassified